2018
DOI: 10.3892/ijo.2018.4608
|View full text |Cite
|
Sign up to set email alerts
|

The novel prognostic marker, EHMT2, is involved in cell proliferation via HSPD1 regulation in breast cancer

Abstract: Molecular classifications of breast cancer (BRC), such as human epidermal growth factor receptor 2 (HER2), luminal A and luminal B, have been developed to reduce unnecessary treatment by dividing patients with BRC into low- and high-risk progression groups. However, these methods do not cover all of the pathological characteristics of BRC, and investigations into novel prognostic/therapeutic markers are thus continually required. In this study, we identified the overexpression of the histone methyltransferase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…The human breast cancer cell line MDA-MB-231 was purchased from the Korean Cell Line Bank (Seoul, South Korea) and cultured at 37 o C in DMEM supplemented with 10% fetal bovine serum (FBS) and 1% penicillin/streptomycin in a humidified atmosphere with 5% CO2 (30).…”
Section: Cell Culturementioning
confidence: 99%
“…The human breast cancer cell line MDA-MB-231 was purchased from the Korean Cell Line Bank (Seoul, South Korea) and cultured at 37 o C in DMEM supplemented with 10% fetal bovine serum (FBS) and 1% penicillin/streptomycin in a humidified atmosphere with 5% CO2 (30).…”
Section: Cell Culturementioning
confidence: 99%
“…EHMT2 is an HMT that is involved in H3K9 dimethylation for the formation of heterochromatin in transcriptional gene regulation. Moreover, in breast, bladder and lung cancer, knockdown of EHMT2 was shown to be involved in cell apoptosis and cell migration/invasion [26][27][28]30]. After treatment with SP in the CRC cell lines, we could not detect any changes in EHMT2 at the transcriptional level, but in western blot analysis, the expression of EHMT2 was significantly reduced ( Fig.…”
Section: Ehmt2 Is a Target For Propionate-induced Cell Apoptosis In Cmentioning
confidence: 88%
“…Among them, euchromatic histone-lysine N-methyltransferase 2 (EHMT2) carried out mono-and dimethylation of histone H3 lysine 9 to generate heterochromatin for the repression of tumor suppressor genes. Knockdown of EHMT2 by siRNA resulted in cell apoptosis, cell cycle arrest, and metastasis in several types of cancer [26][27][28]. Although EHMT2 is an important therapeutic target for CRC treatment, the regulation of EHMT2 expression in CRC, especially the relationship between EHMT2 and the human microbiome, remains elusive.…”
mentioning
confidence: 99%
“…The role of HSP60 in apoptosis is quite conflicting. To support its anti-apoptotic function, knockdown of HSP60 has been found to promote apoptosis in cardiac myocytes, hepatocellular carcinoma (HCC), and breast cancer cells [11,12,32]. In an inducible cardiac-specific HSP60 knockout mouse model, it has been demonstrated that HSP60 deletion in adult hearts leads to an increased number of apoptotic cardiac myocytes, accompanied by altering mitochondrial complex activity, mitochondrial membrane potential (∆Ψm), and reactive oxidative species production.…”
Section: Hsp60 Functions In Normal and Cancer Cellsmentioning
confidence: 99%